Application possibilities of logistics simulation and AI in the case of intermodal terminals - Kováts, Péter; Skapinyecz, Róbert; Tamás, Péter (Advanced Logistic Systems - Theory and Practice, 2024)
Abstract: The paper addresses the fundamental operations and services of intermodal logistics terminals from the ground up. The information collection was primarily based on site visits to several companies, one of which was East-West Intermodal Logistics Service Ltd., and the other was ZÁHONY-PORT Ltd. (Záhony-Logistics and Load Handling Servicing Company). The process continued with data collection, where local leaders and managers provided information through PowerPoint documents and site tours. The entire information gathering process started with the understanding of the main details of the companies, followed by the site visits, and finally, the acquisition of the requested information. The next step was the processing of the collected information, of which the article only describes the analysed results. The application possibilities of AI are closely related to digitization and data collection. Without data, AI cannot be trained for the given task. To increase the available information, we can also use simulation methods (for generating so-called synthetic data), allowing us to introduce artificial intelligence in a relatively new field in a short time.